2015
DOI: 10.1039/c5tx00259a
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure of ozone induced pulmonary injury and the protective role of vitamin E through the Nrf2 pathway in Balb/c mice

Abstract: Ozone (O) in the lower atmosphere is generally derived from various sources of human activity. It has become a major air pollutant in China and has been shown to adversely affect the health of humans and animals. We undertook a study to ascertain the molecular mechanism of ozone induced lung injury in mice and tried to demonstrate the protective mechanism of vitamin E. In this study, mice were exposed to clean air and three different concentrations of ozone. Oxidative stress (reactive oxygen species and malond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This is suggested by the fact that even when both p38 and ERK1/2 inhibitors were used, we did not achieve a complete reduction of expression; moreover, IL-8 inductions in low responders were not influenced by kinase inhibition. This residual IL-8 induction may be due to low-level inputs from other cellular effectors, such as NRF2 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested by the fact that even when both p38 and ERK1/2 inhibitors were used, we did not achieve a complete reduction of expression; moreover, IL-8 inductions in low responders were not influenced by kinase inhibition. This residual IL-8 induction may be due to low-level inputs from other cellular effectors, such as NRF2 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, a essential nutrient for reproduction, is synthesized in plant organisms and composed of eight fat-soluble compounds(α-, β-, γ-, δ-tocopherol, and α-, β-, γ-, δ-tocotrienol) [ 6 ].Some studies have confirmed that oxidative stress plays an important role in the pathogenesis of several allergic diseases, including AR [ 7 ]. Vitamin E is a peroxyl radical scavenger that can protect neurons and respiratory mucosa from oxidant damage, while vitamin E can significantly reduce the incidence of asthma and relieve respiratory mucosa inflammation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vit E has the effect of scavenging free radicals because its phenolic hydroxyl group can donate hydrogen atoms (Lu et al, 2011), and is thus very likely to reduce ROS levels, ameliorate inflammation and control apoptosis. Also, studies have demonstrated that Vit E can trigger an antioxidant pathway, such as the nuclear factor-erythroid 2-related factor 2 (Nrf2) pathway, and provide antioxidant benefits (Zhu et al, 2015). Furthermore, Vit E can play a protective role in cardiovascular health by controlling the levels of adhesion molecules, reducing the activation of monocytes or macrophages, and down-regulating the proliferation of smooth muscle cells (Mocchegiani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%